The Relativity Of Self-Confidence In The Success Of Athletes At PORPROV BALI 2022 - Danardani, Wasti; Hidayat, Syarif; Sari, Suci Nanda (Performa, 2023)
The purpose of this study was to see the relationship between the success rate of the athletes from the Buleleng Regency contingent in the PORPROV Bali event through the confidence possessed by the athletes. This study used all athletes who were registered as the Buleleng Regency contingent as subjects. This research is basic research that will get a description of the condition of the subject. The survey method uses a questionnaire that takes data on the level of confidence. The observation method is used to collect information through document data and events in the field. The data presented from this study is that 80.5% of athletes have high self-confidence and 17.3% moderate. Experience as an athlete > 7 years 33%, 4-7 years 39%, and 0-3 years 28%. Age group 30.25% over 22 years, 54.36% aged 22-17 years, and 15.12% aged under 17 years. This study concludes that the level of self-confidence in the success of athletes is relative, and influenced by the age and experience of the athlete.